2005
DOI: 10.1063/1.1872194
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of polycrystalline bismuth titanate films by Nd3+/W6+ cosubstitution

Abstract: Articles you may be interested inStructural, electrical, and magnetic properties of chemical solution deposited Bi ( Fe 0.95 Cr 0.05 ) O 3 thin films on platinized silicon substrates Structural, ferroelectric, dielectric, and magnetic properties of BiFeO 3 / Bi 3.15 Nd 0.85 Ti 3 O 12 multilayer films derived by chemical solution deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
13
1
Order By: Relevance
“…The Raman mode D at B830 cm À1 can be assigned as A 1g mode, and it is representative of the symmetric Ti-O stretching vibration; the B530 cm À1 (peak C) and B250 cm À1 (peak B) modes can be assigned as B 2g 1B 3g modes originating from the lifting of E g degeneracy, they are ascribed to the opposing excursions of the external apical oxygen atoms of the TiO 6 octahedron and the torsional bending of TiO 6 octahedra, respectively. 5, 23,24 The peak A at B90 cm À1 is due to Bi-O stretching vibration. 23,25 The mode E at B740 cm À1 is typical of pyrochlore phase.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman mode D at B830 cm À1 can be assigned as A 1g mode, and it is representative of the symmetric Ti-O stretching vibration; the B530 cm À1 (peak C) and B250 cm À1 (peak B) modes can be assigned as B 2g 1B 3g modes originating from the lifting of E g degeneracy, they are ascribed to the opposing excursions of the external apical oxygen atoms of the TiO 6 octahedron and the torsional bending of TiO 6 octahedra, respectively. 5, 23,24 The peak A at B90 cm À1 is due to Bi-O stretching vibration. 23,25 The mode E at B740 cm À1 is typical of pyrochlore phase.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Er 3+ –Yb 3+ –W 6+ cosubstitution significantly improved the ferroelectricity of the thin films. It has been reported that W 6+ ion substitution of B ‐site (Ti 4+ ions) can also effectively improve ferroelectric properties of other thin films such as (La 3+ , Nd 3+ , and Pr 3+ )‐doped BiT thin films, Pb(Zr,Ti)O 3 thin films, CaBi 4 Ti 4 O 15 thin films, and SrBi 2 Ta 2 O 9 thin films 15–17 . In BiT‐based thin films, A ‐site substitution of larger Bi 3+ ions by smaller rare‐earth ions in the pseudo‐perovskite layer can result in largely enhanced rotation of TiO 6 octahedra in the a – b plane and a shift of the octahedron along a axis, 27–29 whereas B ‐site substitution of larger Ti 4+ ions by highly valent W 6+ ions can decrease oxygen vacancies to reduce domain pinning, 25,26 and make the polar ions move more easily.…”
Section: Resultsmentioning
confidence: 99%
“…The defects usually act as traps to induce nonradiative transitions, and then results in emission degradation. [22][23][24] The high-valent W 61 substitution with proper concentration can decrease concentration of the oxygen vacancies in the host lattices, 25,26 [15][16][17] In BiT-based thin films, A-site substitution of larger Bi 31 ions by smaller rare-earth ions in the pseudo-perovskite layer can result in largely enhanced rotation…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another case, it is found that B-site substitution in BiT by some ions with higher charge valences such as V 5+ , Nb 5+ and W 6+ could effectively improve the ferroelectric properties by decreasing the space charge density of BiT thin films [4][5][6]. Recently, A-and B-sites cosubstitution in BiT films has also been reported to be more effective in improving ferroelectric properties and fatigue endurance [7][8][9][10][11]. For example, Uchida et al [11] have reported that the Nd 3+ /V 5+ -cosubstituted BiT thin films exhibit ferroelectric properties superior to those of Nd 3+ -substituted BiT.…”
Section: Introductionmentioning
confidence: 94%